COMMUNICATION ANALYSIS OF CHILDREN WITH SPECIAL NEEDS IN SOCIAL STUDIES LEARNING AT SMPN 12 BANDUNG (Descriptive Study at Inclusive Education School Provide) - Nunik Nurachmi, - (2020)
This research is motivated by a phenomenon that occurs in inclusive schools, especially in social studies learning, with special needs students experiencing difficulties in communicating which is a challenge for teachers and their peers to learn to understand and help children with special needs to be able to live together in line with their environment. Various challenges must be sought to deal with various factors that hinder or support both internal and external ABK in developing. Researchers try to describe this special situation in the hope that it can be used as a reference for improvement in dealing with children with special needs who are in the middle of an inclusive school, namely SMPN 12 Bandung, which in fact is a school, the majority of which are normal children. This research is a qualitative descriptive study in class VIII-I SMPN 12 Bandung. Data collection techniques are carried out through observation, interviews, and documentation study. The results of the research findings indicate that the communication skills of children with special needs still experience various disorders and limitations both in verbal, non-verbal, positive and negative communication. Children with special needs have not been able to carry out effective communication activities because they do not have a sense of empathy for their interlocutors, emotional changes in children with special needs are also an unexpected disturbance. Various inhibiting and supporting factors, both internal and external, greatly influence how the development of communication activities for children with special needs in social studies learning. In addition, the various efforts and obstacles faced by social studies teachers as subject teachers also need to be pursued with special support and attention so that ABK's communication skills can be improved and measured clearly in the inclusive school curriculum.